A Study of Cosmology and Its Implications on Islamic Education (Study of Q.S Al-Mulk: 3-4 and Q.S Al-Furqan: 2) - Assajad, Anas (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study examines cosmology in the Qur'an, focusing on verses 3-4 of Surah Al-Mulk and verse 2 of Surah Al-Furqan. This research is a library research. Data sources are obtained by reviewing books, articles, journals, theses, and theses that are related to this research. The main objective is to analyse the basic implications of understanding cosmology in the Qur'an for Islamic education.